Effects of Working Capital Management on Profitability in Manufacturing Firms in Nigeria: Array - Oladipo, Olaniyan Niyi; Adegboyo, Olufemi Samuel; Olugbamiye, Dominic Olorunleke (The Journal of Accounting and Management, 2020)
The study examined the impact of working capital management on profitability in manufacturing firms in Nigeria between the period of 1988 and 2019. The study disaggregated capital management into trade receivables, inventory, cash, and bank balances and trade payables in line with the theories reviewed. The data were obtained from the company review published audit financial report. Based on the mixed level of stationarity of the variables as revealed by the unit root test, the study made use of the auto-regressive distributed lag (ARDL) technique to analyze the data. The bound test revealed that; there was a presence of co-integration (long-run relationship) among the dependent and all the explanatory variables consequently the study estimated the ARDLECM. The result further showed that Cash and Bank Balances (CBB), Trade Payables (TAP) and Trade Receivables (TAR) had a positive and significant impact on the profitability of manufacturing firms in Nigeria which is a clear indication that working capital management has a positive and significant impact on company profitability in Nigeria both in the short and long run. The findings of this study are in tandem with the Keynesian Liquidity preference theory. This study recommends that financial managers increase their working capital and ensure that it is properly managed in order to enhance sales revenue, thus strengthening firm profitability. Furthermore, the study suggests that financial managers should increase investment in working capital to accelerate their productivity so that they can also improve the profitability of the firms.